Confirmatory Factor Analysis of Intrapreneurship in Automatic Identification Technology for Technology Disruption in Thailand - Paitoon, Komkrit; Limsiritong, Karnjira (Community and Social Development Journal, 2022)
The purpose of this research study was to analyze and examine the confirmatory factors in intrapreneurship of automatic identification technology suitable to cope with technology disruption in Thailand. The conceptual framework of the study, derived from the review of related literature, revealed the main factors in the aspects of human resources development and teamwork, leadership and followership, organizational culture, and learning organization. The sample group for the study comprised 420 representatives, including executive staff members in the position of department managers and professional-level employees selected by multiple-stage sampling method. The tool for data collection was a 5-level rating scale questionnaire with the IOC between 0.80-1.00, and SPSS Amos was used for the confirmatory factor analysis. The results of the confirmatory factor analysis asserted that the measurement model of human resources development and teamwork, leadership and followership, learning organization, and organizational culture, respectively, which were all consistent with the empirical data. The fit indices analysis results showed χ2 = 131.80, df = 125, P-value = 0.335, AGFI = 0.947, NFI = 0.980, IFI = 0.999, RMSEA = 0.011, SRMR = 0.009, CFI = 0.999, χ2 / df = 1.049. Based on the results of the research study, the factors examined can be used as a guideline for developing the intrapreneurship of employees in automatic identification technology businesses to embrace the changes and advance the organization to cope with the competitiveness in the future, as well as to come up with creative problem solutions in an effective fashion.